-7(w-4)=-5w+26

Simple and best practice solution for -7(w-4)=-5w+26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(w-4)=-5w+26 equation:


Simplifying
-7(w + -4) = -5w + 26

Reorder the terms:
-7(-4 + w) = -5w + 26
(-4 * -7 + w * -7) = -5w + 26
(28 + -7w) = -5w + 26

Reorder the terms:
28 + -7w = 26 + -5w

Solving
28 + -7w = 26 + -5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '5w' to each side of the equation.
28 + -7w + 5w = 26 + -5w + 5w

Combine like terms: -7w + 5w = -2w
28 + -2w = 26 + -5w + 5w

Combine like terms: -5w + 5w = 0
28 + -2w = 26 + 0
28 + -2w = 26

Add '-28' to each side of the equation.
28 + -28 + -2w = 26 + -28

Combine like terms: 28 + -28 = 0
0 + -2w = 26 + -28
-2w = 26 + -28

Combine like terms: 26 + -28 = -2
-2w = -2

Divide each side by '-2'.
w = 1

Simplifying
w = 1

See similar equations:

| -2w+33=-9(w-6) | | (3+7i)(5+i)= | | -2.6(-2.6)+1.2y=7.8 | | 3z^2-9z/z-3 | | -2.6x=7.8 | | 235+.75d=125+1.63d | | -8x+4(x+2)=4 | | 1/(x^2-64)-3/(x-8)=1/(x+8) | | -2u+4(u-6)=-28 | | 7m-10=-4+5m | | 3x-5x-2= | | 2s-14=-26+5s | | 4r-25=-34+7r | | 9x-26=-5+2x | | 12x^3+16x^2=-5x | | 12*2900+174000= | | -3x-5x-27=29 | | x^2-4x+17= | | (Y-4/y-5)=(y-3/y+1)+1 | | 1/5X^2-2=5 | | -18=7v+9-10v | | 2x+34=45 | | 4(a+7b)+3a= | | 1/2(c+6)+7 | | -2y/9=8 | | 6x-12=180 | | 9x+-16y= | | Lny=lnx+ln(x+14)+lnC | | -30=-5/6v | | 19/18x+1/18x=8x+1/9+17/18x | | 5x+12=180 | | W-2/5=-1/3 |

Equations solver categories